Preferensi Makan Gajah Sumatera (Elephas maximus sumatranus) di Kawasan Hutan Cagar Alam Jantho - Abdullah Abdullah; Dahlian Dahlian; Mukhlisin Mukhlisin (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
The research about food preference of Sumatran elephant have conducted in Jantho Natural Reserve Aceh Besar District inAcehProvincein April to June 2006. The aim of this research was to identified elephant food species vegetation in elephant habitat. This research used direct observation method in 20 transect. We found 22 species eaten Sumatran elephant in Jantho Natural Reserve Aceh Besar District. The food preference consist of Moraceae, 11 species (18,74%), Poaceae, 15 species (15,64%), Arecaceae, 9 species (14,52%), Euphorbiaceae, 6 spesies (9,95%), Mimosaceae, 5 spesies (6,25%), Caesalpiniaceae, 2 spesies (3,30%), Cyperaceae,4 spesies, (3,27%), Bombacaceae, 2 species (3.23 %), Gleicheniaceae, 4 species (3.22%), Zingiberaceae 4 species (2.77%),Fabaceae, 2 species (2.58%), Musaceae, 1 species (2,10%), Apocynaceae, 2 species (1.94 %), Ebonaceae, 1 species (1,70%), Sapindaceae, 1 species (1.41%).